2015
DOI: 10.1039/c5cc02670a
|View full text |Cite
|
Sign up to set email alerts
|

High yield synthesis of high-silica chabazite by combining the role of zeolite precursors and tetraethylammonium: SCR of NOx

Abstract: The synthesis of chabazite with high solid yields is achieved by the rational combination of directing effects of a source of Si and Al coming from USY zeolites and the inexpensive tetraethylammonium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(109 citation statements)
references
References 29 publications
3
106
0
Order By: Relevance
“…Thus, a decrease in the manufacturing costs by finding a less expensive OSDA is a matter of interest for industrial applications of CHA‐related catalysts . In this sense, we recently described the synthesis of high‐silica CHA material by using the less expensive and more environmentally friendly tetraethylammonium (TEA, see Figure B) cation as OSDA by following a simple zeolite‐to‐zeolite transformation with a high‐silica USY zeolite as the initial silicon and aluminium source …”
Section: Resultsmentioning
confidence: 99%
“…Thus, a decrease in the manufacturing costs by finding a less expensive OSDA is a matter of interest for industrial applications of CHA‐related catalysts . In this sense, we recently described the synthesis of high‐silica CHA material by using the less expensive and more environmentally friendly tetraethylammonium (TEA, see Figure B) cation as OSDA by following a simple zeolite‐to‐zeolite transformation with a high‐silica USY zeolite as the initial silicon and aluminium source …”
Section: Resultsmentioning
confidence: 99%
“…SSZ-13 zeolites have been synthesized via various methods, including direct synthesis (from precursors of silica and alumina) and conversion of zeolite Y. For the synthesis of SSZ-13s, various templates, such as N,N,Ntrimethyl-1-adamantanamine iodide (TMAda-I) [5,7], TMAda-OH [8][9][10][11][12], choline chloride [13,14], copper-tetraethylenepentamine (Cu-TEPA) [15][16][17], tetraethylammonium hydroxide (TEA-OH) [18], benzyltrimethylammonium hydroxide [19], and N,N,Ndimethylethylcyclohexylammonium bromide [20] have been used despite several reports of its template-free [21][22][23][24] synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…This explains why hydrothermal aging effects have been so extensively studied [39][40][41][52][53][54]. Prior studies have suggested that Cu/SSZ-13 durability enhancement can be achieved in a number of ways: (1) composition optimization, that is, choosing optimized Si/Al and Cu/Al ratios [31]; (2) zeolite particle size optimization [55]; (3) new synthesis methods development [30,[56][57][58][59]; and (4) introduction of stability enhancement additives. Among these, some appear not to be as useful as others.…”
Section: Towards Rational Design Of Cu/ssz-13mentioning
confidence: 99%
“…From our own experience, too large of a particle size can even be detrimental due to poor heat dissipation during structure directing agent (SDA) combustion that induces rather serious thermal degradation of the SSZ-13 substrate. Also, new Cu/SSZ-13 synthesis methods, including one-pot ones, do not necessarily lead to catalysts with better stability than catalysts prepared with more traditional solution ion-exchange methods [30,[56][57][58][59].…”
Section: Towards Rational Design Of Cu/ssz-13mentioning
confidence: 99%